Escape to the city : fugitive slaves in the antebellum urban South - Müller, Viola Franziska, 1987- (The University of North Carolina Press, 2022)
"Viola Franziska Müller examines runaways who camouflaged themselves among the free Black populations in Baltimore, Charleston, New Orleans, and Richmond. In the urban South, they found shelter, work, and other survival networks that enabled them to live in slaveholding territory, shielded and supported by their host communities in an act of collective resistance to slavery"--